Association between short video exposure and axial length in preschool children: a cross-sectional study - Chenshu LI; Senlin LIN; Sha LUO; Hao CHEN; Yi SUN; Hong JIANG; Yingnan JIA (Zhongguo gonggong weisheng)
ObjectiveTo investigate the exposure time and content characteristics of short videos among preschool children and analyze their association with axial length, in order to provide a reference for myopia prevention and control in preschool children. MethodsFrom April to June 2023, 326 preschool children from 36 classes in one kindergarten each in Pudong New district and Xuhui district, Shanghai city, were enrolled in this study. Online questionnaires were distributed to parents to collect information on children's sociodemographic characteristics, home electronic device environment, and daily behaviors. Axial length, height, and weight were measured on-site. A tablet computer equipped with a "Children′s Screen Exposure" application was used to accurately measure the duration and content of children′s electronic screen use within one week. Data were analyzed using t-tests, linear regression, and quantile regression. ResultsThe axial length of boys [(22.69 ± 0.65) mm] was significantly longer than that of girls [(22.00 ± 0.72) mm]. Axial length increased significantly with age (β = 0.269, P < 0.001), height (β = 0.346, P < 0.001), weight (β = 0.342, P < 0.001), and daytime sleep duration (β = 1.2×10−3, P = 0.03). Sixty-three (19.33%) preschool children were exposed to short videos, with children's programs accounting for the highest proportion of viewing time (23.18%). 48.40% of the children's viewing time was PG-rated or above, requiring parental guidance or unsuitable for children. The vast majority of the content viewed by children was non-educational (96.09%) and rapidly changing (82.75%). Children also watched a large proportion of reality-based content (52.13%). Children who spent more time watching slow-switching videos had longer axial lengths (β = 0.0385, P = 0.04). ConclusionsPreschool children are exposed to short videos, mostly children′s programs, non-educational content, and rapidly changing content. The viewing time is mainly spent on reality-based content and PG-rated or above content. Children who spend more time watching slow-switching short videos have longer axial lengths.